2015
DOI: 10.1080/03601234.2015.1062648
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of mancozeb, chlorothalonil, captan, fluopyram, boscalid, and difenoconazole toDidymella applanataisolates from Serbia

Abstract: Field isolates of Didymella applanata, the causal agent of spur blight of raspberry, were evaluated in vitro for their sensitivity to mancozeb, chlorothalonil, captan, fluopyram, boscalid and difenoconazole. A total of 10 isolates, collected during 2013 at five localities in the major raspberry growing region in Serbia, and characterized as copper hydroxide, dithianon, and tebuconazole (sensitive), pyraclostrobin (sensitive or highly resistant) and fluazinam (sensitive or moderately resistant), were used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Difenoconazole has been used to control many cereal, vegetable and fruit diseases including potato early blight in China since 1998 and ∼10% of its global production is sold in Chinese markets recent years 1 ,2 (Zheng et al, 2013). However, this observation is consistent with previous results showing that difenoconazole is still effective in controlling many plant pathogens such as A. solani , Rhizoctonia cerealis , Colletotrichum capsici , Didymella applanata , and Ceratocystis fimbriata (Reuveni and Sheglov, 2002; Gopinath et al, 2006; Mirkovic et al, 2015; Wang et al, 2016; Scruggs et al, 2017) and suggests that there is a low risk of developing difenoconazole resistance in many plant pathogens (Hamada et al, 2011; Fonseka and Gudmestad, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Difenoconazole has been used to control many cereal, vegetable and fruit diseases including potato early blight in China since 1998 and ∼10% of its global production is sold in Chinese markets recent years 1 ,2 (Zheng et al, 2013). However, this observation is consistent with previous results showing that difenoconazole is still effective in controlling many plant pathogens such as A. solani , Rhizoctonia cerealis , Colletotrichum capsici , Didymella applanata , and Ceratocystis fimbriata (Reuveni and Sheglov, 2002; Gopinath et al, 2006; Mirkovic et al, 2015; Wang et al, 2016; Scruggs et al, 2017) and suggests that there is a low risk of developing difenoconazole resistance in many plant pathogens (Hamada et al, 2011; Fonseka and Gudmestad, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…It was also reported that higher dose of Mancozeb have negative effect on plant growth and activity of mycorrhizal symbiosis (Saleh 2006, Chaurasia 2014. According to Kackar et al (1997) and Mirkovic et al (2015) chronic oral feeding of Mancozeb has produced dose dependent toxicity and death of animal by structural and functional changes like significant increase in thyroid, body weight ratio and histopathological changes. Easton et al (2001) reported that by the effect of Mancozeb fungicide novel proteins being induced and stress were increased.…”
Section: Resultsmentioning
confidence: 99%
“…Pesticide toxicity can be determined using several methods based on various types of microorganisms, such as Didymella applanata , Vibrio fischeri , Selenastrum apricornotum and Daphnia magna. For instance, the Daphnia magna motility assay has been used to determine pesticide toxicity . In this study a toxicity test using the bioluminescent bacteria Vibrio fischeri was chosen because it is widely used, quick, and easy to perform …”
Section: Introductionmentioning
confidence: 99%